Development of Entrepreneurship Textbooks Using Project-Based Learning for Economic Education Graduate Students - Rakmawati, Dwi Yuli; Wulandari, Siti Sri; Rafida, Veni; Wulandari, Ruri Nurul Aeni (Technium Social Sciences Journal, 2024)
The S2 Economics Education Study Program produces graduates who can have a career as educators in the field of Economic Education and can have a career as Entrepreneurs and Practitioners in the field of Economics. The Entrepreneurship Studies course provides insight to students about the basic concepts of the economy, merketing, and interaction between economic actors so that students are able to understand the issues that occur and are able to solve the entrepreneurial problems they are facing. Entrepreneurship Studies lecture activities so far still tend to lecture activities by lecturers. This causes student participation in discussion activities to be limited. The purpose of the research is to develop a 4-D learning model in the Entrepreneurship Studies course to develop learning tools supported by project-based learning modules to improve the quality of learning so as to produce graduates with high economic insight and problem-solving skills. This study uses a 4-D instructional design development model which includes the stages of define, design, develop, disseminate. Data collection uses validation techniques and questionnaires with instruments including graph validation sheets, material validation sheets and student response questionnaires